NADPH diaphorase expression in superior colliculus of developing, aging and visually deafferented rats - Vercelli, Alessandro; Boido, Marina; Jhaveri, Sonal (Italian Journal of Anatomy and Embryology, 2012)
We have studied the development of NADPH-diaphorase activity in the retinorecipient layers of the superior colliculus (SC) in rats from embryonic day 17 to adulthood, during aging, and following neonatal tetrodotoxin injection or unilateral eye removal in the neonatal or in the adult animal. In the superficial SC, NADPH-d activity is first seen in neurons on postnatal day (P) 4; over the next two weeks, enzyme expression increases gradually, in cells as well as in the neuropil. By P12-14, around the time of eye opening, NADPH-d reactivity increases dramatically. In parallel, the dendrites of many NADPH-d-positive neurons in the superficial gray layer, more or less randomly distributed at first, gradually align their orientation relative to the dorsoventral axis. The pattern of NADPH-d activity in the superficial layers of the SC (i.e. stratum griseum superficiale and stratum opticum) is adult-like by the fourth week of age. Deafferentation of the superficial SC, both in the neonatal and adult rat, and block of retinal activity lead to reduction in the size of the SC and changes in NADPH-d-positive neurons, including dendrite misorientation, decreased cell size and reduced number. Some of these changes are seen also in the aging animal. These results document a protracted and progressive increase in the development of NADPH-d expression in the SC. Our results suggest a strong influence of retinal afferents and activity on the development and maintenance of NAPHD-positive neurons in the retinorecipient layers of the SC, where NO can act as a retrograde signal to carve the terminal arbors of retinal axons.